Traffic and Technological Solution of the Urban and Suburban Railways of the City of Split - Antun Stipetić; Nenad Klarić; Slavko Šerić (Promet - Traffic&Transportation, 1970)
In accordance with the advanced concepts of humanisationand rationalisation of traffic, an increasing number of activitiesis being undertaken in order to calm the traffic in thecentral parts of the cities and to increase it in the suburban districts.The development of transport means is accompanied bythe need to redefine the segment of urban area due to greatermobility of the citizens. One of the efficient systems of organisingtraffic is the urban railway. The aim of the urban railway isto alleviate the burden on the urban and suburban traffic routesaccommodating excessive road traffic and to provide rationalintegration into the system of urban public transit.The traffic network in the Split-Kastela area has beenmainly constructed at times of very low traffic requirements,and today it cannot satisfy the increased traffic needs. Becauseof the impossibility to substantially increase the capacity of theurban roads, lack of parking space, and also due to environmentalrequirements, no increase in the share of the personaltransport of passengers should be expected. In such conditionspublic transport of passengers can save the urban agglomerationfrom total traffic and environmental collapse.The railways is precisely the mode of transport that shouldrepresent in the future the backbone of the public urban andsuburban transport in the Split-Kastela region.